Galectin-8 binds to LFA-1, blocks its interaction with ICAM-1 and is counteracted by anti-Gal-8 autoantibodies isolated from lupus patients - Lucas Vicuña (Biological Research, 2013)
Galectin-8 belongs to a family of mammalian lectins that recognize glycoconjugates present on different cell surface components and modulate a variety of cellular processes. A role of Gal-8 in the immune system has been proposed based on its effects in immune cells, including T and B lymphocytes, as well as the presence of anti-Gal-8 autoantibodies in the prototypic autoimmune disease systemic lupus erythematosus (SLE). We have previously described that Gal-8 induces apoptosis in activated T cells interacting with certain β1 integrins and this effect is counteracted by the anti-Gal-8 autoantibodies. Given that Gal-8 can potentially interact with several glycoproteins, here we analyzed the β2 integrin Lymphocyte Function-Associated Antigen-1 (LFA-1), which is involved in leukocyte cell adhesion and immunological synapses. We show by GST-pull down assays that Gal-8 interacts with LFA-1 and this interaction is inhibited by anti-Gal-8 autoantibodies isolated from SLE patients. In cell adhesion assays, Gal-8 precluded the interaction of LFA-1 with its ligand Intracellular Adhesion Molecule-1 (ICAM-1). These results suggest that Gal-8 can exert immunosuppressive action not only by inducing apoptosis in activated T cells but also by negatively modulating the crucial function of LFA-1 in the immune system, while function-blocking autoantibodies counteract these effects.